CHARACTERISTICS AND FATTY ACID PROFILE JELAWAT FISH MEAL (Leptobarbus hoevenii) WITH DIFFERENT COOKING METHODS - Ngafif Fatuh Zahroh; Edison '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research aimed to determine the chemical characteristics and fattyacid profile jelawat fish meal with different cooking methods. This research usedthe experiment method. Cooking methods used in this research T0 (control), T1(steaming) dan T2 (presto). Proximate analysis of three samples were tested by thesoxhlet method and kjeldahl method. Analysis of fatty acid used GasCromatography method. The average value of proximate jelawat fish meal withdifferent cooking methods T0, T1 and T2 a row are moisture content 6.42%, 8.38%,8.70%, ash 9.62%, 5.22%, 3.52%, protein conten 65.10%, 65.30%, 68.80%, andfat conten 14.60%, 9.45%, 5.80%. Based on the analysis, there are 25 kinds offatty acids identified in jelawat fish meal. The fatty acids consist of 10 kinds ofsaturated fatty acids and 15 kinds of unsaturated fatty acids. The results showedthat jelawat fish meal with different cooking methods T2 have a fatty acid contenwith each total unsaturated fatty acids 46.22%.Keywords: fatty acid, cooking methods, jelawat fish meal.